Early Macro Divergence from Micro: Keynes vs Hayek, Fisher and Friedman - Gillman, Max (Journal of Reviews on Global Economics, 2015)
The paper presents facts and theory of the Great Depression that led to the clash of the Neoclassical ideas of Fisher and Hayek with the new interventionalist concept of Keynes. The Keynesian Cross arose to explain how government could create new investment and allow the economy to rise from Depression. Fisher and Hayek instead emphasized banking and monetary policy with "reflation" of price stabilization, upon which Friedman built. The Great Recession policy today echoes more firmly the ideas of Fisher and Hayek in avoiding another depression.